UMP, NIU forged a cooperation, offering engineering technology - UMP, PNC
Universiti Malaysia Pahang (UMP) created history when it signed a memorandum of understanding (MoU) with Northern Illinois University (NIU), in offering an engineering technology programme, on May 20, 2011 at De Kalb Illinois, US.